The new negotiating edge : the behavioral approach for results and relationships - Kennedy, Gavin. (Nicholas Brealey, 1998)
This book is about: Negotiation as a universal process; Attitudes, Beliefs, and Behaviors of Negotiators; The Haggle; ...